Smart FRP reinforcements for long-term health monitoring in infrastructure - Kalamkarov, Alexander L.; Saha, Gobinda; Georgiades, Tasos (My University, 2004)
Smart glass fiber-reinforced polymer (FRP) reinforcements with embedded Fabry-Perot fiber-optic sensors are pultruded and investigated in both laboratory and environmental extreme conditions. Various mechanical (quasi-static and cyclic loads, fatigue loads, long- and short-term creep), thermal (from -40° to +60°C), and severe environmental (alkaline solutions with pH12.8) loads are imposed onto the smart FRP tendons, prior to their application in laboratory-designed concrete beams. A comprehensive testing program is followed for the beams, including thermal exposure during and after concrete curing phases, static and cyclic failure-induced loadings. In all testing programs, the data obtained from the interferometric Fabry-Perot fiber-optic sensors are compared to those from an extensometer, an electrical resistance strain gage, and an LVDT. The study shows that the response, in terms of internal mechanical strain, against applied mechanical and structural loads up to the failure of the concrete beams can be steadily obtained using embedded smart FRP rebars. These results have higher accuracy when compared with other strain-measuring counterparts.
Keywords: Pultrusion; Reliability (Engineering); Structural health monitoring; Concrete--Testing